The occurrence of Alaria alata mesocercariae in wild boars (Sus scrofa) in north-eastern Poland. (August 2020) - Strokowska, Natalia; Nowicki, Marek; Klich, Daniel; Bełkot, Zbigniew; Wiśniewski, Jan; Didkowska, Anna; Chyla, Piotr; Anusz, Krzysztof
Abstract: Various species of mammals, including humans and wild boars, can serve as paratenic hosts of Alaria alata mesocercariae – Distomum musculorum suis (DMS). Cases of DMS can be reliably detected by the recent introduction of the A. alata mesocercariae migration technique (AMT). The aim of this study is to present current data on the occurrence of DMS in wild boars in north-eastern Poland, and to compare the findings with those obtained in other European countries. A. alata was identified in 98 of 221 (44.3%) tissue samples of wild boar taken from five provinces in north-eastern Poland during the hunting seasons 2015–2016 and 2016–2017 based on AMT analysis. Positive results were found in all studied regions, but the percentage of infected individuals ranged from 26.3% in the Pomorskie province to 65.5% in the Warmińsko-Mazurskie province. The mean number of larvae exceeded seven larvae per 30 g sample for three provinces: Pomorskie, Mazowieckie and Lubelskie. In turn, lower values were found in the Warmińsko-Mazurskie province (3.3 larvae per 30 g), and the lowest in the Kujawsko-Pomorskie province (1.8 larvae per 30 g). The occurrence and intensity of A. alata infestation in wild boars was found to depend on the environment in which they live. Neither the sex or the age of the wild boar appeared to influence the occurrence nor the intensity of infestation. Graphical abstract: Image 1 Highlights: High percentage (44.3) of Alaria alata in samples of wild boars in Poland. High prevalence of A. alata infestation in wild boars compared to other reports. Sex does not affect the risk or intensity of infestation by A. alata in wild boars. Age does not affect the risk or intensity of A. alata infestation in wild boars. A. alata poses a potential risk for wild boar consumers in Poland.